2018
DOI: 10.1016/j.jtcvs.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Late left ventricular rupture as a complication of NeoChord implantation for mitral valve repair

Abstract: GORE-TEX artificial chordae tendineae and NeoChord implants. Central MessageComplications are just part of the route to developing a new surgical technique. Exhaustive knowledge of the procedure, moreover, is required to improve its reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Traditional surgical MV repair with ePTFE sutures attached to the PM heads has been proven to be safe, stable, and durable up to 20 years after surgery, with only a few isolated cases of suture failure, most of them in the setting of late rupture up to 14 years after surgery. 55 Nevertheless, Heuts et al 56 and Kassem et al 57 have recently reported cases of late neochordae rupture after transapical neochordae repair. Our results showed that the maximum systolic tension experienced by a single neochorda was approximately 1.21 N. This neochorda tension is significantly lower than the failure tension of ePTFE CV-4 sutures, which is approximately 16.36 N. 58 Thus, intracardiac tensile force alone would be unlikely the sole driving force of transapical neochordae rupture under the specific loading conditions and neochordae configurations modeled in this single patient model.…”
Section: Neochordae Biomechanics and Clinical Perspectivementioning
confidence: 99%
“…Traditional surgical MV repair with ePTFE sutures attached to the PM heads has been proven to be safe, stable, and durable up to 20 years after surgery, with only a few isolated cases of suture failure, most of them in the setting of late rupture up to 14 years after surgery. 55 Nevertheless, Heuts et al 56 and Kassem et al 57 have recently reported cases of late neochordae rupture after transapical neochordae repair. Our results showed that the maximum systolic tension experienced by a single neochorda was approximately 1.21 N. This neochorda tension is significantly lower than the failure tension of ePTFE CV-4 sutures, which is approximately 16.36 N. 58 Thus, intracardiac tensile force alone would be unlikely the sole driving force of transapical neochordae rupture under the specific loading conditions and neochordae configurations modeled in this single patient model.…”
Section: Neochordae Biomechanics and Clinical Perspectivementioning
confidence: 99%
“…The overwhelming majority of the ruptures in these 58 patients were type III [2,3,7,8,18,19,22,[26][27][28]. Failure of transapical off-pump mitral valve repair with Neo-chordal implantation (DS 1000; NeoChord Inc, St. Louis Park, Minnesota, USA) have introduced a new subset of patients with rupture site located between the base of the papillary muscle and ventricular apex [17]. Since the etiopathogenesis, anatomic location and therapeutic strategies are different, the corresponding author (UKC) proposes this group to be classified as type IV ventricle rupture and to be included in the existing classification of Treasure and Miller ( Table 2, Figures 1 and 2).…”
Section: IVmentioning
confidence: 99%
“…In this technique, the NeoChord was fixed within the left ventricle between the base of the papillary muscle and the apex. Following chordal rupture, a MVR was performed using a standard 29mm Carpentier-Edwards Perimount Magna Ease bioprosthesis (Edwards Lifesciences Corporation, Irvine, California), but the patient succumbed to late left ventricular rupture on postoperative day 6 due to exsanguinating bleeding [17].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 2 more Smart Citations